2022
DOI: 10.1108/ilt-02-2022-0054
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surface waviness on the static performance of journal bearing with CuO and CeO2 nanoparticles in the lubricant

Abstract: Purpose This study aims to investigate the impact of surface waviness on the static performance parameters of hydrodynamic journal bearings operating with lubricants containing copper oxide (CuO) and cerium oxide (CeO2) nanoparticles. Design/methodology/approach The static performance parameters of bearings with surface waviness and the addition of nanoparticles in lubricants were calculated using the nondimensional form of Reynolds equation and finite element method. Static performance parameters are calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Thus, the chances of metal‐to‐metal contact reduce in these regions thereby enhancing the journal‐bearing dynamic and stability performance with waviness in the circumferential direction in full region and pressure‐reducing region. Further, as we increase the circumferential wave number, the bearing with surface waviness behaves like a plain/smooth bearing because as we increase the number of waves, the crust and trough formed on the bearing surface have a very close gap distance 23 . Also, the lubricant flowing in between the crest and trough of waves in a circumferential direction act as a reservoir in the clearance space of the bearing system and further, these reservoirs entrap wear debris/foreign particles and prevent damage to the surface as wear debris may abrade the rest of bearing surface 43 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the chances of metal‐to‐metal contact reduce in these regions thereby enhancing the journal‐bearing dynamic and stability performance with waviness in the circumferential direction in full region and pressure‐reducing region. Further, as we increase the circumferential wave number, the bearing with surface waviness behaves like a plain/smooth bearing because as we increase the number of waves, the crust and trough formed on the bearing surface have a very close gap distance 23 . Also, the lubricant flowing in between the crest and trough of waves in a circumferential direction act as a reservoir in the clearance space of the bearing system and further, these reservoirs entrap wear debris/foreign particles and prevent damage to the surface as wear debris may abrade the rest of bearing surface 43 …”
Section: Resultsmentioning
confidence: 99%
“…Yang et al 22 observed the dynamic behaviour of the wave bearing using the finite difference method and Reynolds equation and revealed that waviness influences the bearing stability. Bangotra and Sharma 23,24 reported that the surface waviness and the use of lubricant additives and the partial surface waviness enhance the static performance of journal bearings.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results revealed an increase in maximum pressure and load carrying capacity of the journal bearing by adding NPs to the base oil especially for the higher volume fraction of NPs. Bangotra and Sharma [30] investigated the impact of surface waviness on the static performance parameters of hydrodynamic journal bearings operating with lubricants containing copper oxide (Cu0) and cerium oxide (CeO 2 ) NPs. The static performance parameters were calculated for different waviness numbers and various wave amplitudes with variable viscosities of nanolubricants using a relationship between the relative viscosity, temperature, and weight fraction of NPs developed from experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…It was discovered that irregularities increase the value of minimum fluid film thickness and lubricant flow. Bangotra and Sharma 11,12 reported that due to the surface waviness, the load capacity increases, and the COF reduction and surface waviness in the pressure region is more effective in the circumferential direction than the axial direction.…”
Section: Introductionmentioning
confidence: 99%